An Evaluation of an Experiential Learning Program in Global and Indigenous Health: The University of Manitoba's Queen Elizabeth II Diamond Jubilee Scholarship Program - Natalie D. Riediger PhD; Monica Cyr RD, MSc; Javier Mignone PhD (SAGE Publishing, 2020)
We conducted a mixed-methods outcome evaluation to examine student experiences and learning in the University of Manitoba's Queen Elizabeth II Diamond Jubilee Scholarship Program in Global and Indigenous Health. Our scholarship program is a bi-directional, 3-month international experiential learning program, including both undergraduate and graduate students, with associated online course focused on community engagement. Students completed a semi-structured narrative report at the conclusion of their funding related to their experience and learning. The Likert questions were analyzed descriptively and student responses to the open-ended questions were utilized for thematic analysis. Also included in this paper is a summary of our lessons learned through program administration. A total of 38 students completed the program between 2016 and 2018, with 95% reporting that they either met or exceeded their goals in the program. Three overarching and inter-related themes emerged in our thematic-analysis of students' narrative reports, including success through relationships and new perspectives, challenges of the unfamiliar , and personal growth through strong emotions . Many students reported personal growth as their greatest success and linked this with new perspectives and awareness of how different contexts shaped their understanding of health issues. Overcoming challenges in their placements contributed to students' confidence in their ability to problem-solve. Overall, students reported value in their experiential learning, which further supports the growing trend to incorporate both experiential learning and formal education in community engagement in public health pedagogy. However, international experiential learning requires considerable financial and human resource commitments to ensure its success.